2015
DOI: 10.1111/ffe.12296
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue assessment of high‐frequency mechanical impact (HFMI)‐treated welded joints subjected to high mean stresses and spectrum loading

Abstract: The fatigue strength of welded joints can be improved with various post‐weld treatment methods. High‐frequency mechanical impact treatment is a residual stress modification technique that creates compressive residual stresses at the weld toe. However, these beneficial residual stresses may relax under certain loading conditions. In this paper, previously published fatigue data for butt and fillet welded joints subjected to high stress ratios and variable amplitude cyclic stresses were evaluated in relation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…However, benefit from HFMI-treatment remained even for Smin = -0.8fy with respect to similarly loaded AW state. This is in agreement with experimentally observed benefit from HFMI-treatment under VA loading [14,21,35,36]. Similarly, both the fatigue damage analysis and experiments [8][9][10] have indicated benefit from HFMI under R = 0.5 CA loading.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, benefit from HFMI-treatment remained even for Smin = -0.8fy with respect to similarly loaded AW state. This is in agreement with experimentally observed benefit from HFMI-treatment under VA loading [14,21,35,36]. Similarly, both the fatigue damage analysis and experiments [8][9][10] have indicated benefit from HFMI under R = 0.5 CA loading.…”
Section: Discussionsupporting
confidence: 88%
“…Current International Institute of Welding (IIW) fatigue design recommendations on post-weld improvement take residual stress relaxation into account by limiting allowable nominal stresses in these structures [5]. However, previous work [14], where available experimental high stress ratio and variable amplitude (VA) loading data were analysed, has indicated that the proposed peak stress limit for HFMI-treated joints subjected to fully-reversed loading [2] is too conservative in the case of variable amplitude (VA) loading.…”
Section: Introductionmentioning
confidence: 99%
“…From residual stress relaxation point of view, it is expected that relaxation will occur during one critical cycle due to either high mean stress or large compressive stress. As stated in [6], Equation 2and (3) fit available high stress ratio data reasonably well without being overly conservative.…”
Section: Fig 12mentioning
confidence: 64%
“…damage sum FAT characteristic fatigue class in MPa corresponding to 2×10 6 cycles at failure with a survival probability of 95% based on two-sided confidence limits at a confidence level of 75% ( High-frequency mechanical impact (HFMI) is an effective and user-friendly means for improving the fatigue strength of welded steel joints. In addition, the method provides potential for lightweight design, as the fatigue strength of HFMI-treated joints increases with increasing steel strength [1,2].…”
mentioning
confidence: 99%
See 1 more Smart Citation